Ginger Essential Oil for Postharvest Quality of Datterino Tomato: Effect of Immersion Duration and Storage Temperature - Adams, Abdul Rahaman; Adama, Abdul Razak; Thadius, Tambu kuunuori; Barau , Bashir (Journal of Postharvest Technology, 2018)
Tomatoes are considered one of the most important components of human diet and there are several issues that affect their shelf-life. This study was conducted to examine the effect of immersing Datterino Tomato in ginger essential oil on qualitative traits during storage. Fruits were stored at 5ºC, 7ºC and 26.9ºC for 14 days. The experiment was laid out using Completely Randomized Design with two replications. The response parameters measured were, cumulative percentage weight loss, titratable acidity, total soluble solids, firmness, taste index and consumer acceptance. There were cases where both Temprature and Essential oil had significant difference. Fruits stored at 26.9ºC lost weight faster than those stored at 5ºC and 7ºC. Samples treated with ginger essential oil however experienced the lowest weight loss as compared to the control samples at all temperatures. The results obtained on firmness, TSS, flavour and acceptance demonstrated significant difference at P ≤ 0.05 due to both Ginger essential oil and temperature treatments. Fruit firmness at the end of the experimental period revealed that, samples treated with Ginger essential oil for 30 minutes recorded the highest firmness values. Results indicated that, samples treated for 20 minutes recorded the lowest decline in TSS. The results demonstrated that no significant difference at P ≤ 0.05 was found on both TA, TI and sweetness. Based on the results from the study conducted, Ginger essential oil immersion combined with lower temperatures of 5ºC and 7ºC demonstrated effectiveness in maintaining postharvest quality of Datterino tomato fruit.